The Determinant Factors of Community Involvement in Becoming a Customer of the Waste Bank in Tamanjaya Village, Tamansari District, Indonesia - Nissa Noor Annashr; Andy Muharry; Dadan Yogaswara; Nisa Khoerunisa (School of Postgraduate Studies, Diponegoro Univer, 2024)
Tamansari District has the 4th largest waste generation in Tasikmalaya City in 2021, namely 34.93 tons per day. The purpose of this study was to analyze the determinant factor of community involvement in becoming a customer of the Lestari Waste Bank. This research was included in the analytic observational study using a cross sectional design. The population in this study was all households living in RW 13, Tamanjaya Village, totaling 102 people. Sampling using total sampling technique. Therefore, the sample size involved in the study was 102 people. Data collection was carried out through an interview process with a questionnaire instrument. The data analysis consisted of univariate analysis, bivariate analysis using chi-square and fisher's exact tests and multivariate analysis using multiple logistic regression tests. The results showed that education level (p = 0.049; OR = 2.889), knowledge (p = 0.0001; OR = 6.333), attitude (p = 0.0001), socialization (p = 0.012; OR = 4.146), external support (p = 0.0001; OR = 14.074) were proven to be determinant factors for community involvement in becoming customers of the waste bank. The determinant factor most related to community involvement in becoming a customer of the Waste Bank was external support (OR = 8.636).